2023
DOI: 10.1017/s2045796023000604
|View full text |Cite
|
Sign up to set email alerts
|

Specific effects of five subtypes of childhood maltreatment on suicide behaviours in Chinese adolescents: the moderating effect of sex and residence

Abstract: Aims Although childhood maltreatment has been widely supported to be a robust predictor of suicide behaviours, the effects of different childhood maltreatment subtypes remain controversial and inconclusive. Moreover, whether the effects differ by sex in urban and rural adolescents is still unknown. This study aimed to quantify the associations between five subtypes of childhood maltreatment and different suicide behaviour involvement. Methods A multistage cluster sampling method was adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…With a few exceptions 43 , few paper suggested that physical neglect had a significant impact on mental health; but we should note that those with physical neglect has high comorbidity of ACEs (e.g., childhood poverty, emotional abuse/neglect) in this study. Many studies suggested that emotional abuse and neglect had great impacts on mental health 44 47 . Such comorbidity might strengthen the impact of physical neglect.…”
Section: Discussionmentioning
confidence: 99%
“…With a few exceptions 43 , few paper suggested that physical neglect had a significant impact on mental health; but we should note that those with physical neglect has high comorbidity of ACEs (e.g., childhood poverty, emotional abuse/neglect) in this study. Many studies suggested that emotional abuse and neglect had great impacts on mental health 44 47 . Such comorbidity might strengthen the impact of physical neglect.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). More detailed information regarding Stage 2 to Stage 5 was described in our other publication ( Peng et al., 2023 ).…”
Section: Methodsmentioning
confidence: 99%